Targeted Therapies and Pharmacologic Advances in Mucous Membrane Pemphigoid: A Comprehensive Review - Busol, Vera Nikolaevna; Kudryashov, Nikita Victorovich (Dermatology Practical & Conceptual, 2025)
Introduction: Mucous membrane pemphigoid (MMP) is a rare autoimmune bullous dermatosis which predominantly affects the mucous membranes and, occasionally, the skin. The exact pathogenesis of MMP remains unclear and should be considered as a unique phenomenon, which involves the formation of subepithelial blisters and fibrosis.Objectives: This narrative review aimed to summarize the pharmacological agents which showed efficacy in the management of MMP but that are not included in the guidelines.Methods: We conducted a search on Google Scholar, PubMed, and the Web of Science databases concerning articles published in English on the management of MMP between January 2000 and February 2025; all the sourced articles were full-text reviewed.Results: We included 13 articles. The studied pharmacological agents are classified as immunosuppressive agents (leflunomide, sirolimus, daclizumab) and biologics (daclizumab, dupilumab, omalizumab, bevacizumab, aflibercept, cenegermin); the immunosuppressant leflunomide and the antimalarial agent hydroxychloroquine are also classified as disease-modifying antirheumatic drugs. Other pharmacological agents (colchicine, corticotropin, varenicline, lifitegrast) exert miscellaneous mechanisms.Conclusion: Considering the severity of the condition, progressive fibrosis, and resistance to therapy, more research is required in relation to the pathogenesis of MMP and the efficacy and safety profile of novel pharmacological options. Pharmacological agents should provide the achievement and maintenance of remission with minimal adverse effects. A broader spectrum of pharmacological agents will allow a personalized approach and more alternatives, in particular for recalcitrant cases, failure of the previous therapy, and in patients with MMP and malignancy.